Nurses’ perception of occupational stress and its influencing factors: A qualitative study - Adib-Hajbaghery, Mohsen (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: Studies have shown that nurses are under considerable job stress, which can lead to health disorders and failure in duties. Stressors of nursing have been studied in some of quantitative studies; however, a few investigators have studied the nurses’ life experiences in this regard. The current qualitative research aimed to understand the nurses’ experiences and perceptions of job-related stress. MATERIALS AND METHODS: This qualitative study was conducted in 2010-2011 by using the content analysis technique. Data were collected through individual deep interviews with 19 nurses working in hospitals affiliated to Kashan University of Medical Sciences. The content of data was analyzed by the Krippendorff method. RESULTS: Three categories were emerged including ‘nurses’ perception from the job stress, “professional interest”, and “prioritizing career over family life”. The first category included the following subcategories of “being in constantly alarm situation,” “lack of experience”, “dignity and social status”, “lack of proper logistics”, “shortage of nurses”, “Irregularities in the organization,” “directors of nursing performance,” “undesirable relations among colleagues,” and “the patients conditions all have effects on the nurses’ level of professional stress. CONCLUSION: The study participants defined job stress as a condition in which a nurse is under pressure so that the quality of care and the nurses’ personal and family life is interrupted. Being under continuous pressure, low social dignity, and the manner of nurse managers were among the important sources of job stress. Providing appropriate logistics, improving the coordination within hospital subsystems, and improving the managers and nurses relationships may decrease the stressors in nursing profession.